ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN BERWIRAUSAHA INDUSTRI PERCETAKAN (STUDI KASUS WIRAUSAHA INDUSTRI PERCETAKAN DI KOTA JAMBI) - Hermansyah Hermansyah; Dahmiri Dahmiri (Jurnal Manajemen Terapan dan Keuangan, 2019)
This study aims to determine the factors that influence the success of the Printing Industry business in Jambi City. The population in this study was the printing industry entrepreneur with 55 respondents. Sample collection was carried out by distributing questionnaires with census techniques to 55 entrepreneurs who already have a printing industry in the city of Jambi. This research uses Multiple Linear Regression analysis tools. The results showed that the factors that had a significant influence were the Marketing and Sales Factors, and Government Regulation Factors. Factors that did not have a significant effect were Opportunity Factor, Human Factor (HR), Financial Factor, Organizational Factor, Planning Factor, Business Management Factor, Administrative Factor, and Business Record Factor. And the most dominant factor is the Marketing and Sales Factor. With good marketing and large sales, business success will be even greater.